SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN OBJEK WISATA DI PULAU LOMBOK DENGAN METODE PROFILE MATCHING (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Lombok Island, as a major tourist destination in Indonesia, offers various attractions including popular tourist villages. So far, there has been no proper guide or guideline for selecting tourist attractions in Lombok Island that match the preferences and needs of tourists, resulting in inaccuracies in choosing attractions that suit visitors' preferences, with added criteria from previous research including comfort, beauty, facilities, distance, cost, time, transportation, culinary, crowd levels, and limited available information. This study aims to develop a decision support system for selecting tourist attractions in Lombok Island using the Profile Matching method. The Profile Matching method is used with an analytic hierarchy approach to determine criteria weights, enabling the system to rank and recommend tourist attractions based on user preferences. The research will demonstrate which tourist villages have the highest values that tourists will choose. The research results indicate that the developed decision support system can assist tourists in selecting tourist attractions that match their desires.